Growth characteristics of the European hake, Merluccius merluccius (Linnaeus, 1758), inhabiting northeastern Mediterranean - Girgin, Hulya; Basusta, Nun (Inst Oceanografiju I Ribarstvo, 2020)
In this study, the age and some growth characteristics of the European hake, Merluccius merluccius, from the northeastern Mediterranean were examined during 2015-2016 fishing season. A total of 661 European hake ranging from 9.8 to 51.6 cm in total length was captured by commercial trawler. Female/male ratio was 1/1.15. Age determination was conducted using the sagittal otoliths. Ages of examined individuals ranged from 1 to 7 years. The von Bertalanffy growth parameters fitted to the average measured total lengths-at-age for each sex separately and estimated as L-infinity = 93.98 cm, k= 0.114 year(-1), t(0) = -0.597 year fir females, as L-infinity = 77.65 cm , k= 0.153 year(-1), t(0) = -0.343 year for males and as L-infinity = 84.44 cm, k = 0.135 year(-1), t(0) =-0.469 year for combined sexes. The growth performance value (() of the European hake population was computed as 2.98 for combined sexes. Mean condition factor value for population was 0.654 +/- 0.021; the highest condition factor was found as 1.01 in fish at age 7.
Zna?ajke rasta osli?a, merluccius merluccius (Linnaeus, 1758.), u sjeveroisto?nom dijelu sredozemnog mora
Keywords: European hake; Merluccius merluccius; age; growth; northeastern Mediterranean; condition factor